Physical properties evaluation of ceramic tiles produced with the addition of ceramic production residues - Coal ash Avaliação das propriedades físicas de revestimentos cerâmicos produzidos com resíduo da indústria cerâmica (Cinza pesada de carvão mineral) - Souza D.H.* (2015)
© 2015, Universidade Federal do Rio de Janeiro. All rights reserved.The ash is a solid waste generated in ceramic processing, being one of the outcomes of burning pulverized coal. The chemical composition of ash consists of a mixture of oxides, especially Al2O3, SiO2 and Fe2O3, and other species like calcium, magnesium, sulfates or other combinations. In many companies, the residual ash is transported to landfills, which are licensed by environmental agencies. With the increasing current produc-tion of ceramic tiles, the landfills have a limited lifetime, so the companies must search for other expensive alternatives for ash deposition. Henceforth, the addition of ash to the raw material, besides contribution to reduction of the environment impact, may also reduce the total costs, by decreasing the amount of raw mate-rial demanded in process and the amount of residual ash to be deposed. So, the objective of this study was to evaluate the physical properties of ceramic tiles produced with the addition of coal ash. Specimens were pre-pared by adding 1 to 30% of ash to mass base. The specimens were stored in refractory recipients and fired in a tunnel furnace at the temperature of 1084 °C in a 29 hours cycle. Physical parameters were analyzed for slip and specimens after firing. The results were compared with standards according to NBR 13818. The re-sults showed that properties of specimens produced with the addition of 1 up to 10% of ash are in accord-ance with NBR 13818. For samples with higher percentages of ash, e.g. above 4%, some parameters did not achieve the norm standards. The formation of “black core” was the main problem for these samples.